Assessment of dynamic change in psychotherapy with adolescents - Elisabeth Ness; Hanne-Sofie Johnsen Dahl; Peter Tallberg; Svein Amlo; Per Høglend; Agneta Thorén; Jens Egeland; Randi Ulberg (BMC, 2018)
Abstract Background Diagnostic interviews and questionnaires are commonly used in the assessment of adolescents referred to child and adolescent mental health services. Many of these rating scales are constructed for adults and focus on symptoms related to diagnosis. Psychodynamic Functioning Scales (PFS) focus on relational aspects and how the patients handle affects and solve problems, rather than manifest symptoms. As these aspects are considered important for mental health, the PFS were developed to assess change in adults, consistent with the relational and intrapsychic concepts of dynamic psychotherapy. The scales describe internal predispositions and psychological resources that can be mobilized to achieve adaptive functioning and life satisfaction. PFS consist of six subscales; the relational subscales Family, Friends and Romantic/Sexual relationships and the dynamic subscales Tolerance for Affects, Insight and Problem-solving Capacity. PFS has been used for the first time as a measure of change in adolescent psychotherapy. This study examines the reliability of PFS when used to assess adolescents' level of relational functioning, affective tolerance, insight, and problem-solving capacities. Methods Outpatient adolescents 16-18 years old with a major depressive disorder were included in the First Experimental Study of Transference work in Teenagers (FEST-IT). They were evaluated before and after time-limited psychodynamic psychotherapy with an audio-recorded semi-structured psychodynamic interview. Based on the audio-tapes, raters with different clinical background rated all the available interviews at pre-treatment (n = 66) and post-treatment (n = 30) using PFS. Interrater reliability, the reliability of change ratings and the discriminability from general symptoms were calculated in SPSS. Results The interrater reliability was on average good on the relational subscales and fair to good on the dynamic subscales. All pre-post changes were significant, and the analyses indicated discriminability from general symptoms. The interrater reliability on PFS (mean) and Global Assessment of Functioning were good to excellent. Conclusion Based on the interrater reliability in our study, PFS could be recommended in psychotherapy with adolescents by experienced clinicians without extensive training. From the post-treatment evaluations available, the scales seem to capture statistically and clinically significant changes. However, the interrater reliability on dynamic subscales indicates that subscales of PFS might be considered revised or adjusted for adolescents. Trial registration First Experimental Study of Transference-Work-In Teenagers (2011/1424 FEST-IT). ClinicalTrials.gov Identifier: NCT01531101